2016
DOI: 10.3928/00989134-20160212-08
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effect Sizes of the Revised Daily Engagement of Meaningful Activities Intervention for Individuals With Mild Cognitive Impairment and Their Caregivers

Abstract: A nurse-led intervention, Daily Engagement of Meaningful Activities (DEMA), was evaluated for feasibility and effect sizes in a two-group randomized pilot study with 36 MCI patient-caregiver dyads (17 DEMA and 19 attention control). Effect sizes were estimated on 10 outcomes: dyad functional ability awareness congruence; patients’ meaningful activity performance satisfaction, confidence, depressive symptoms, communication satisfaction, physical function, life satisfaction; and, caregivers’ depressive symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 31 publications
0
50
0
Order By: Relevance
“…The goal of this systematic review was to determine whether nonpharmacological interventions (ie, cognitive, psychological, nutritional, and physical interventions) offered to people with MCI or to their caregiver are efficient in reducing the caregiver's burden and psychological symptoms and/or to improve the caregiver's QoL. Four clinical trials focusing on cognitive interventions and multidimensional interventions (including elements from both cognitive and psychological intervention) were included in the systematic review, 9,11,31,32 3 of which were randomized control trials. 9,31,32 Overall, the nonpharmacological interventions included in this study did not have an impact on burden, but 2 studies showed an effect in reducing depressive symptoms of caregivers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of this systematic review was to determine whether nonpharmacological interventions (ie, cognitive, psychological, nutritional, and physical interventions) offered to people with MCI or to their caregiver are efficient in reducing the caregiver's burden and psychological symptoms and/or to improve the caregiver's QoL. Four clinical trials focusing on cognitive interventions and multidimensional interventions (including elements from both cognitive and psychological intervention) were included in the systematic review, 9,11,31,32 3 of which were randomized control trials. 9,31,32 Overall, the nonpharmacological interventions included in this study did not have an impact on burden, but 2 studies showed an effect in reducing depressive symptoms of caregivers.…”
Section: Resultsmentioning
confidence: 99%
“…There is limited generalizability of the results of the 4 published studies due to the fact that recruitment was performed in memory, neurology, or neuropsychology clinics. 9,11,32 Another important problem is the omission of long-term follow-up measures assessing the efficacy of the intervention to prevent the worsening of the caregiver's burden and psychological symptoms or QoL. 11,31 Also, objective and subjective burdens were not measured consistently in all clinical trials.…”
Section: Limitationmentioning
confidence: 99%
“…The study design was a two‐group randomized, controlled pilot of DEMA in a sample of PwMCI–caregiver dyads. Study aims were related to feasibility, acceptability, and effect size of the DEMA intervention compared to an information support (IS) group (Lu et al, ). In this article, we report quantitative and qualitative findings specifically related to our research questions: What are PwMCI and their caregivers’ perceptions of satisfaction (usefulness, ease of use, acceptability) with the DEMA intervention compared to the IS attention control group?…”
Section: Design and Methodsmentioning
confidence: 99%
“…The authors explained such findings as relating to the possible floor effect due to the lesser disease impact at the early stage of MCI. Another pilot study evaluated the effects of Daily Engagement of Meaningful Activities among the PwMCI and caregiver dyads 10. Problem-solving therapy was used to support the care dyads to identify and implement meaningful activities through goal achievement and problem-solving in six bi-weekly sessions.…”
Section: Introductionmentioning
confidence: 99%